Development and evaluation of Pleurotus pulmonarius mycelium as encapsulated liquid spawn for cultivation / Norjuliza Mohd Khir Johari - Norjuliza , Mohd Khir Johari (2019)
Pleurotus pulmonarias also known as grey oyster mushroom is the most popular edible mushroom in Malaysia. Typically, commercial cultivators use grain spawn to inoculate into steriled fruiting substrate but contamination rate and attraction to pest during spawn running is high. Good quality spawn should be free from diseases, fast colonisation with high yield potential. Therefore, to overcome the low quality spawn problems, the application of submerged culture technology followed by encapsulation of mycelium is proposed. Growers can easily utilize the spawn using this technology without the need for an expensive spawn inoculator equipment. The aim of this study is to optimize production and delivery of P. pulmonarius mycelium to be used as spawn for cultivation. An optimised culture medium at initial pH of 5.5 consisting of brown sugar, 2%; baker yeast, 1%; spent grain extract, 1%; potassium dihydrogen phosphate (KH2PO4), 0.05%; dipotassium hydrogen phosphate (K2HPO4), 0.05%; magnesium sulfate (MgSO4.7H20), 0.05% and Tween 80, 0.5% successfully supported high growth of 11.89 ±3.80 g/ L dried mycelial biomass rapidly in 60 hours at 28°C in a 2-L stirred tank bioreactor. The optimum storage time determined for soluble starch P. pulmonarius encapsulated mycelial broth (SS-PPEMB) was 10 days stored in sterile distilled water at 4°C (C4 condition) exhibiting 100% germination on sawdust fruiting substrate. The potential of SS-PPEMB as spawn was assessed on sawdust fruiting substrate in polyethylene bags and the spawn run rate observed was 3.80 mm/day with biological efficiency of 180.99 ± 13.16 % even after storage at 10 days. As a conclusion, this study has successfully produced a high quality spawn with low risk of contamination and high yield. This technology is also applicable to other species of mushroom cultivated by mushroom industry.